COMPARISON OF THE PARADIGM INTEGRATION OF SCIENCE AT STATE ISLAMIC UNIVERSITIES - Mukhlas Nugraha; Muhammad Rafii (Journal of Applied Transintegration Paradigm, 2021)
Abstract The discourse of knowledge integration found its momentum when there was a change in higher education from IAIN to UIN. Various conceptual proposals began to be debated academically, armed with a universal spirit and expanding the contribution of Islamic universities to science, universities that have held university status finally began to discuss the formulation of the integration of religion and science broadly. However, although the integration of knowledge is the starting point for academic anxiety within UIN, the interpretation and articulation are different. UIN Yogyakarta with the integration-interconnection paradigm, UIN Jakarta has the concept of reintegration of knowledge, UIN Malang with the integration of its knowledge, and UIN Jambi articulates it as the transtegration of knowledge. The diversity of this paradigm is claimed to have its own distinction. This article attempts to compare the concept of integration of knowledge applied at UIN Yogyakarta, UIN Jakarta, UIN Malang, and UIN Jambi. Sources of data are obtained from various relevant literatures, discussions, seminars, and journals to examine fundamentally the concepts of each offered paradigm. The researcher analyzes the basic concepts of the scientific paradigm applied in a number of Islamic universities in order to answer the differences and can be compared with other concepts of integration of knowledge.